Synthesis of Novel Aryl-Substituted Acetylenic Monoterpene Analogues by Sonogashira Coupling - Rinat Gubaidullin; Lyudmila Parfenova (Chemistry Proceedings)
The synthesis of new aryl-substituted acetylenic monoterpene derivatives was carried out by the Sonogashira reaction. The reactions proceed in the presence of PdCl2(PPh3)2, CuI and Et3N and provide aryl-substituted acetylenic monoterpenes with an isolated yield of 70–82%.